Evaluation of the better operative outcome software tool to predict cataract surgical outcome in the early postoperative follow-up - M. Lecumberri; C L. Moser; J. Loscos-Arenas (BMC Ophthalmology, 2023)
Abstract Background Cataracts are the world’s leading cause of avoidable blindness. In low-income countries, there are high rates of poor follow-up, which makes it very difficult to monitor surgical outcomes. To address this issue, the Better Operative Outcome Software Tool (BOOST Cataract app) predicts outcome on the first postoperative day and provides specific advice to improve outcomes. The aim of the study is to evaluate the ability of the BOOST Cataract app to categorise surgical outcomes and to analyse the possible factors that contribute to its performance. This was a prospective observational study performed at the General Hospital of Hospitalet of Llobregat. Results A total of 126 cataracts were included. Patients had a mean [SD] age of 75.8 [12.19] years, and 52% were females. Manual small-incision cataract surgery was involved in 57% and phacoemulsification in 43%. Thirty-eight percent of eyes presented significant corneal oedema on day 1. The BOOST Cataract app succeeded in categorising the final outcome in 65.6% of the eyes and in 93,4% of the eyes with good outcome.The agreement between the BOOST and UDVA outcomes was 0.353 (p< .000). The level of agreement improved to 0.619 (p< .000) in eyes with clear corneas. Success obtained by BOOST for both types of surgery was not statistically different. Eyes that obtained a good outcome on day one after surgery and eyes with clear cornea had 37 times higher odds (95% CI 6.66, 212.83) and 12 times higher odds (95% CI 3.13, 47.66) of being correctly categorised by the BOOST Cataract app than eyes that obtained a suboptimal (moderate and poor) outcome and eyes with corneal oedema on day 1. Conclusions The BOOST Cataract app is an e-Health tool designed to address issues of measuring quality in low- and middle-income settings. Although its reliability is limited to eyes that obtain a good outcome and with clear corneas on day 1, the use of the tool on a regular basis facilitates monitoring and reporting outcomes when clinical data collection is challenging due to low postoperative follow-up rates.